New records of disk-winged bats Thyroptera tricolor Spix, 1823 and T. devivoi Gregorin, Gonçalves, Lim & Engstrom, 2006 (Chiroptera: Thyropteridae) for the Brazilian Amazonia and Cerrado - Semedo, Thiago Borges Fernandes; Garbino, Guilherme Siniciato Terra; Ardente, Natália; Colas-Rosas, Paul François; Torres, Mariene Almeida; Rossi, Rogério Vieira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
We present new records for the disk-winged bats Thyroptera tricolor and T. devivoi in central and northern Brazil. Records of T. tricolor are from Aripuanã, Usina Hidrelétrica (UHE) Colíder (both in the northern Mato Grosso state) and Santana do Araguaia (southern Pará state). New records of T. devivoi are from a Cerrado area in the Rio Manso, Rio Quilombo (both in Mato Grosso state) and from an Amazon rainforest area at Juruti (Pará state). The records of Thyroptera devivoi for Pará and Mato Grosso are the first ones for these states and the records from the latter are based on two specimens previously identified as T. discifera. Based on the new identifications, we argue that T. discifera does not occur in the Cerrado.